“Parto pretérmino: Factores de riesgo en el hospital regional de Loreto “Felipe arriola Iglesias” Punchana – Iquitos” - Cuadros Cáceres, Rubén Jorge (1996)
The present study of applied type correlation, with prospective data collection, was performed at the Regional Hospital of Loreto "Felipe Arriola Iglesias" Punchana from December 1, 1994 to November 30, 1995, to determine maternal, fetal risk factors And the most important ovulatory variables related to preterm birth, as well as neonatal morbidity and mortality During the study period, 2,054 births occurred, of which 148 were preterm infants with a frequency of 7. 20%, risk factors for childbirth (OR = 8.21), low socioeconomic status (OR = 7.42), maternal age over 40 years (OR = 4.37), multiparity (OR = 4.08), single marital status (OR = OR = 2.98), history of abortion (OR = 2.51), grade of primary education (OR = 2.07) CONCEPTIONAL MATERNOS: Vaginitis (OR = 24.98), absence of prenatal control (OR = 10.25), (OR = 6.50). FETAL AND OVULAR: Congenital malformation, multiple pregnancy (OR = 22.97), oligoamnios (OR = 8.40) and premature rupture of membranes (OR = 2.41). The specific rate of neonatal morbidity was 69.41% and the specific rate of neonatal mortality was 57.65%; To reduce the incidence of preterm birth, it is necessary to extend prenatal control to all pregnant women, to improve the socioeconomic and educational level of the population, as well as to make an early diagnosis of preterm delivery for a better management of this disease.